CalliSpheres® drug-eluting beads trans-bronchial artery chemoembolization in treatment of advanced primary lung cancer with massive hemoptysis - LIU Song; BAI Xiangyun; WANG Qingdong; YU Guangji; LI Ling; ZHU Zhizhen (Zhongguo linchuang yanjiu, 2023)
Objective To explore the efficacy and safety of CalliSpheres® drug-eluting beads trans-bronchial artery chemoembolization (DEB-BACE) . Methods A retrospective analysis was conducted on 45 patients with advanced primary lung cancer complicated with massive hemoptysis treated in Linyi Cancer Hospital from December 2019 to December 2021. All patients received bronchial artery embolization (BAE) and were divided into observation group (n=24) and control group (n=21) according to different embolization materials. DEB-BACE using CalliSpheres® drug-eluting beads loading 40-60 mg of epirubicin was performed in observation group, and BACE with 8Spheres® blank microspheres was given in control group. The control of hemoptysis, tumor response, the survival time and the related adverse reactions were observed and compared between two groups. Results There was no significant difference in hemostatic success rate between observation group and control group (87.5% vs 85.7%, P＞0.05) . The median duration of nonmassive hemoptysis in observation group was statistically longer than that in control group (96 days vs 50 days, P＜0.01) . At two months after embolization therapy, the objective response rate (83.3% vs 38.1%) in observation group were significantly higher than those in control group (P＜0.05) . The fever, chest tightness and chest pain related to the embolization treatment disappeared after symptomatic treatment in two groups, and there was no statistical difference in adverse reactions between two groups (P＞0.05) . No serious complications such as spinal cord injury and cerebral embolism occurred in two groups. By the end of September 30, 2022, the median overall survival in observation group (10 months) was statistically higher than that in control group (6 months) (P＜0.01) at a follow-up of 2-25 (9.97±5.41) month. Conclusion In the treatment of advanced lung cancer with massive hemoptysis, DEB-BACE can achieve higher tumor response rate, longer survival time without hemoptysis and total survival time compared with conventional BAE.